Gandalia Art of Banyumas : a Socio-cultural Change - Febrianto, Aji Sofian; Sunarto, Sunarto; Utomo, Udi (Universitas Negeri Semarang, 2018)
Gandalia is one example of musical arts which can endure changes and times. It is a typical Banyumas traditional music which was used to play a specific Gandalia song, an agricultural pest repellent song. Its instruments has similar forms to musical instruments called Angklung, which are made from bamboo. The instruments produce a unique rhythm. At first, Gandalia was used as a means to drive agricultural pests away, but in its development, it becomes a musical performance. This change is interesting to be studied from the socio-cultural point of view. The writer, therefore, studied the functional change of Gandalia musical instruments based on the socio-cultural change which occur in the society who supports it. In writing this article, the research method applied is qualitative method, a method of collecting data by applying some techniques such as interview, observation, and documentation, while the validity of the data is checked by using triangulation, member checking, and rich and thick description.Milesr that, the data are analyzed using qualitative analysis of Miles and Huberman that is an interactive model of data analysis including some stages such as the process of data collecting, data reduction, and data presentation and verification. The research result shows that Gandalia music which, at first, was a means of driving pests away, now becomes one of the performance arts. This change is influenced by the socio-culture of the society who supports Gandalia art. They are the people of Tambaknegara, Banyumas Regency. This socio-cultural change has created a more complex form of Gandalia art.